Effect of Decortication for Empyema Thoracis by Video Assisted Thoracic Surgery on Pulmonary Function (Journal of National Institute of Neurosciences Bangladesh, 2022)
Background: Video-assisted thoracoscopic surgery (VATS) is the minimally-invasive procedure for decortication which may improve pulmonary function postoperatively.Objective: The aim of the study was to find out the long time outcome in relation to pulmonary function after VATS decortication.Methodology: This cohort study was conducted in the Department of Thoracic Surgery at National Institute of Diseases of the Chest and Hospital, Dhaka, Bangladesh during the period of March 2018 to July 2020. After fulfillment of enrollment criteria patients were selected. Spirometric value (FVC, FEV1, FEV1/FVC) were evaluated before and after operative procedure and during subsequent three follow ups.Results: FVC changes between preoperative and postoperative consecutive three follow up periods show significant difference (p